Cardiac autonomic reactivity to acute ingestion of glucose and fructose in healthy subjects - Savitri Sidddanagoudra; Shantala Herlekar; Ashwini Doyizode; Pooja Hittalamani (Wolters Kluwer Medknow Publications, 2022)
Context: Excess intake of fructose in the form of soft drinks and corn syrup is increasing and considered as an interest of community health. The effects on the cardiovascular system due to acute intake of these sugars have not well-studied in humans. Animal studies show a clear relation between ingestion of simple sugar and pathogenesis of hypertension and metabolic disorders. Ingestion of glucose increases cardiac output (CO) without change in blood pressure (BP) and reduces total peripheral resistance (TPR). Fructose increases heart rate (HR), BP, and CO without reduction in TPR. Aims: This study aimed to evaluate the cardiac autonomic reactivity by HR variability (HRV) of basal and after ingestion of water, glucose, and fructose. Settings and Design: Randomized crossover study. Subjects and Methods: The study included 30 healthy both-gender subjects of age 18-24 years. In three separate sessions, HRV responses to one of the three test drinks were measured. (1) plain water, (2) 60 g glucose, and (3) 60 g fructose. Each drink is made up of 500 ml solution by addition of water. Statistical Analysis Used: Analysis was performed by two-way ANOVA. Results: Fructose ingestion showed decreased RR interval (RRI) (696.8 ± 102.7), increased Low frequency power (LF)/High frequency power (HF) (0.94 ± 0.2) compared to glucose (RRI: 747.0 ± 75.1, LF/HF: 0.89 ± 0.3) and water (RRI: 877.1 ± 107.0, LF/HF: 0.84 ± 0.1). Conclusions: Acute consumption of these simple sugars may result in different cardiac autonomic responses, fructose stimulating decreased vagal response.